The Influence of Jamaluddin Al-Afgani's Thought on the Pan Islamism and Islamic Modernism Movement in Indonesia - Rendra Khaldun (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
The current of modernism that was carried by Europe with its characteristic ―rationalistic-empirical‖ exerted a very striking influence in the midst of Islamic society. The spread of modernism became more prominent when this concept of thought found its place among Islamic thinkers—as if it were a new school in the dynamics of Islamic thought. One concrete form of the impact of this current of modernist thought in Islam is the birth of one of the reformist-modernist schools; requires every Islamic society to study, understand, reconstruct and create a new format that is able to answer every problem of the Ummah from every line of life. The moderism of Islamic thought underwent significant changes and gained a new world when Islamic thinkers used this model of thought in fulfilling religious guidance to the need for religion in solving various problems that began to surface, necessitating a new formula to fix the socio-politics of the Islamic community which in fact was becoming obsolete and outdated, as proclaimed by Jamaludin al-Afghani. The implication of al-Afghani's modernism is that of the Pan-Islamic concept of carrying a centralized form of government led by a caliph, but still incorporating contemporary ideas. Afghani offers a democratic system as the right way out as the ideal form of an Islamic state. More concretely, Afghani even gave consideration to using a republican system of government.